Å leve i et minefelt . Living in a Mine Field - Gjertsen, Marit (Videomaker, 2006)
Verzio FF Submission An Vi lives in Somloth, a small village in Cambodia. She has been the sole provider for her eight daughters since her husband passed away killed by a landmine - one of the many thousands of landmine victims in rural Cambodia. Poverty however, pushes An Vi to start cultivating a piece of land herself knowing that it is covered with landmines.